WORK FAMILY CONFLICT, WORK STRESS AND ORGANIZATIONAL COMMITMENT IN AFFECTING THE PERFORMANCE OF PHYSICAL NURSES IN PADANG CITY - Yulihardi Yulihardi; Amrullah Amrullah; Syaiful Syaiful (PENANOMICS: International Journal of Economics, 2022)
The purpose of this study was to analyze the effect of work family conflict, work stress and organizational commitment partially and simultaneously in influencing the performance of nurses. The object of the research is the nurse of the RSJ (Psychiatric Hospital). at Padang City. The sample in this study were 58 female nurses who were married and served in 3 shifts. This study used a closed questionnaire, with a Likert scale and data from the questionnaire was processed using the SPSS version 22 program. The results of this study were: (1) The work family conflict variable had no significant effect on the nurse's performance, (2) the work stress variable had a significant effect on the nurse's performance. , (3) The variable of organizational commitment has a significant effect on the performance of nurses, and (4) The variables of work family conflict, work stress and organizational commitment simultaneously affect the nurses performance of the RSJ. In Padang City. these variables can explain the nurse's performance variable by 30.4%. The rest can be explained by other variables not observed in this study. The conclusion is that partially the work family conflict variable has no effect, while work stress and organizational commitment have an effect, jointly affecting the performance of nurses. Future research is also expected to be carried out on a wider research object so that the research results can be generalized. In addition, it is also necessary to add other variables in predicting nurse performance these variables can explain the nurse's performance variable by 30.4%. The rest can be explained by other variables not observed in this study. The conclusion is that partially the work family conflict variable has no effect, while work stress and organizational commitment have an effect, jointly affecting the performance of nurses. Future research is also expected to be carried out on a wider research object so that the research results can be generalized. In addition, it is also necessary to add other variables in predicting nurse performance these variables can explain the nurse's performance variable by 30.4%. The rest can be explained by other variables not observed in this study. The conclusion is that partially the work family conflict variable has no effect, while work stress and organizational commitment have an effect, jointly affecting the performance of nurses. Future research is also expected to be carried out on a wider research object so that the research results can be generalized. In addition, it is also necessary to add other variables in predicting nurse performance jointly affecting the performance of nurses. Future research is also expected to be carried out on a wider research object so that the research results can be generalized. In addition, it is also necessary to add other variables in predicting nurse performance jointly affecting the performance of nurses. Future research is also expected to be carried out on a wider research object so that the research results can be generalized. In addition, it is also necessary to add other variables in predicting nurse performance